In vivo metabotropic glutamate receptor type 5 abnormalities localize the epileptogenic zone in mesial temporal lobe epilepsy - Lam, Jack; DuBois, Jonathan M.; Rowley, Jared; González‐Otárula, Karina A.; Soucy, Jean‐Paul; Massarweh, Gassan; Hall, Jeffery A.; Guiot, Marie‐Christine; Rosa‐Neto, Pedro; Kobayashi, Eliane (Annals of neurology, 2019)
Objective Surgical specimens from patients with mesial temporal lobe epilepsy (MTLE) show abnormalities in tissue concentrations of metabotropic glutamate receptor type 5 (mGluR5). To clarify whether these abnormalities are specific to the epileptogenic zone (EZ), we characterized in vivo whole‐brain mGluR5 availability in MTLE patients using positron emission tomography (PET) and [11C]ABP688, a radioligand that binds specifically to the mGluR5 allosteric site. Methods Thirty‐one unilateral MTLE patients and 30 healthy controls underwent [11C]ABP688 PET. We compared partial volume corrected [11C]ABP688 nondisplaceable binding potentials (BPND) between groups using region‐of‐interest and whole‐brain voxelwise analyses. [18F]Fluorodeoxyglucose (FDG) PET was acquired in 15 patients, for whom we calculated asymmetry indices of [11C]ABP688 BPND and [18F]FDG uptake to compare lateralization and localization differences. Results [11C]ABP688 BPND was focally reduced in the epileptogenic hippocampal head and amygdala (p < 0.001). Patients with hippocampal atrophy showed more extensive abnormalities, including the ipsilateral temporal neocortex (p = 0.006). [11C]ABP688 BPND showed interhemispheric differences of higher magnitude and discriminated the epileptogenic structures more accurately when compared to [18F]FDG uptake, which showed more widespread hypometabolism. Among 23 of 25 operated patients with >1 year of follow‐up, 13 were seizure‐free (Engel Ia) and showed significantly lower [11C]ABP688 BPND in the ipsilateral entorhinal cortex. Interpretation [11C]ABP688 PET provides a focal biomarker for the EZ in MTLE with higher spatial accuracy compared to [18F]FDG PET. Focally reduced mGluR5 availability in the EZ might reflect receptor internalization or conformational changes in response to excessive extracellular glutamate, supporting a potential role for mGluR5 as therapeutic target in human MTLE. Ann Neurol 2019; 1–11 ANN NEUROL 2019;85:218–228.